Analisis Produktivitas Pekerja Sebelum dan Sesudah Implementasi Standard Operating Procedure pada PT. Multi Indowood - Isaac Frederic Chrisanto (Jurnal Titra, 2022)
PT. Multi Indowood is a company producing furniture such as chairs, tables, and cabinets. The company implemented standard operating procedure (SOP) to increase productivity, and this paper aims to analyze the implementation. The research focus on determining the success of SOP implementation in warehouse improvement and increased worker productivity. Time and worker activity data were collected from three machines in the warehouse using the work sampling method for each process. The results of the evaluation analysis showed that the SOP was successfully implemented, with an increase in worker productivity and a decrease in cycle time and non-productive activities. The increase in worker productivity was also made by reducing activities classified as unnecessary non-value added and necessary non-value-added. Solution creation needs to be done to reduce the actvitiy classified as unnecessary non-value added and necessary non-value-added. There are five solution designed to control SOP implementation and reduce non-productive activity in the warehouse.